Low‐Temperature‐Processed 9% Colloidal Quantum Dot Photovoltaic Devices through Interfacial Management of p–n Heterojunction. Issue 8 (2nd February 2016) - Azmi, Randi; Aqoma, Havid; Hadmojo, Wisnu Tantyo; Yun, Jin‐Mun; Yoon, Soyeon; Kim, Kyungkon; Do, Young Rag; Oh, Seung‐Hwan; Jang, Sung‐Yeon
Abstract : Low‐temperature solution‐processed high‐efficiency colloidal quantum dot (CQD) photovoltaic devices are developed by improving the interfacial properties of p–n heterojunctions. A unique conjugated polyelectrolyte, WPF‐6‐oxy‐F, is used as an interface modification layer for ZnO/PbS‐CQD heterojunctions. With the insertion of this interlayer, the device performance is dramatically improved. The origins of this improvement are determined and it is found that the multifunctionality of the WPF‐6‐oxy‐F interlayer offers the following essential benefits for the improved CQD/ZnO junctions: (i) the dipole induced by the ionic substituents enhances the quasi‐Fermi level separation at the heterojunction through favorable energy band‐bending, (ii) the ethylene oxide groups containing side chains can effectively passivate the interfacial defect sites of the heterojunction, and (iii) these effects occur without deterioration in the intrinsic depletion region or the series resistance of the device. All of the figures‐of‐merit of the devices are improved as a result of the enhanced built‐in potential (electric field) and the reduced interfacial charge recombination at the heterojunction. The benefits due to the WPF‐6‐oxy‐F interlayer are generally applicable to various types of PbS/ZnO heterojunctions. Finally, CQD photovoltaic devices with a power conversion efficiency of 9% are achievable, even by a solution process at room temperature in an air atmosphere. The work suggests a useful strategy to improve the interfacial properties of p–n heterojunctions by using polymeric interlayers. Abstract : High‐efficiency colloidal quantum dot photovoltaic devices (CQDPVs) are developed by improving the interfacial properties of p–n heterojunctions using a conjugated polyelectrolyte as an interface modifier. The conjugated polyelectrolyte effectively improves charge extraction efficiency by enhancing internal electric field and passivating interfacial defects. Using this strategy, CQDPVs with 9% efficiency are able to be fabricated through room temperature solution process.